Assessoria em serviço social: uma análise a partir do Conselho Tutelar de São Borja (RS) - (:unkn) unknown (Universidade Federal do Pampa, 2018)
Counseling in Social Service to Guardianship (s) is still a subject little explored in academic scope, which justifies the present production, in view of the materialization of strategies to strengthen the TC, as a strategic organ in guaranteeing the rights of children and adolescents. This Course Conclusion Paper (TCC) discusses the process of Counseling in Social Service (SS) to Guardianship Councils from the SãoBorne context, as a strategic possibility to support the actions of the collegiate in promoting the Doctrine of Integral Protection. The general objective was to analyze the mediations that the Social Service builds during the process of technical advice to the Sanitation Council of São Borja, with a view to broadening the theoreticalacademic discussion as well as strengthening the advisory service as a space conducive to the materialization of the Ethical- Political of the profession. The specific objectives were built with the perspective of apprehending the socio-historical process of edification of the technical advisory actions in Social Work in the Tutelary Council; to investigate how advisory actions in (SS) can contribute to the political strengthening of the Guardianship Council with the Child and Adolescent Rights Guarantee System (SGDCA). Identify the challenges and potential of Social Work counseling. Reflect on how the praxis of the social worker materializes in the process of advising the Guardianship Council. The present study has as methodology the explanatory qualitative approach, where for the analysis of reality, the dialecticalcritical method and its nuclear categories were used: Historicity, Totality, Contradiction and Mediation. In the year 2018 for the data collection, the strategy of semi-structured interviews was used, where a questionnaire was constructed containing questions that made it possible to apprehend the dynamics of reality from the institution. To analyze the data was used the Method of Systematization of the Practice of Maria Mercedes Gagneten (1987). The study revealed the low scientific production on the subject; the timid insertion of the Social Work professionals in these social-occupational spaces. It revealed the presence of difficulties for the professional exercise, as the loss of the historical records of the institution, "Atas do CT"; lack of documented information regarding the resources available in the municipality; the fragility of administrative flows and the fulfillment of demands; the absence of systematic data CT; however proving to be fertile soil for professional intervention research. Being that from this reality, the Advice in Social Service begins to contribute with organ, in the support, the construction of different strategies in order to overcome these obstacles. It is concluded that there is a need for the presence of Social Welfare professionals in the TC (s) in order to broaden and consolidate the discussion regarding the Doctrine of Integral Protection to children and adolescents.
Keywords: Serviço Social; Conselhos tutelares; Trabalho qualificado; Social service; Tutelary councils; Skilled work; CNPQ::CIENCIAS SOCIAIS APLICADAS